Nutrition for swimming - Shaw, G.; Boyd, K. T.; Burke, L. M.; Koivisto, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
Swimming is a sport that requires considerable training commitment to reach individual performance goals. Nutrition requirements are specific to the macrocycle, microcycle, and individual session. Swimmers should ensure suitable energy availability to support training while maintaining long term health. Carbohydrate intake, both over the day and in relation to a workout, should be manipulated (3-10g/kg of body mass/day) according to the fuel demands of training and the varying importance of undertaking these sessions with high carbohydrate availability. Swimmers should aim to consume 0.3g of high-biological-value protein per kilogram of body mass immediately after key sessions and at regular intervals throughout the day to promote tissue adaptation. A mixed diet consisting of a variety of nutrient-dense food choices should be sufficient to meet the micronutrient requirements of most swimmers. Specific dietary supplements may prove beneficial to swimmers in unique situations, but should be tried only with the support of trained professionals. All swim- mers, particularly adolescent and youth swimmers, are encouraged to focus on a well-planned diet to maximize training performance, which ensures sufficient energy availability especially during periods of growth and development. Swimmers are encouraged to avoid rapid weight fluctuations; rather, optimal body composi- tion should be achieved over longer periods by modest dietary modifications that improve their food choices. During periods of reduced energy expenditure (taper, injury, off season) swimmers are encouraged to match energy intake to requirement. Swimmers undertaking demanding competition programs should ensure suitable recovery practices are used to maintain adequate glycogen stores over the entirety of the competition